The answer is 2,000.
Considering a gas tank's full capacity of 14.5 gallons, after using 1.5 gallons, subtract this from the initial amount to find how much gasoline remains. This leaves us with an inequality 0 ≤ G ≤ 13, where G represents the gasoline left in the tank.
The subject of this question is the calculation of quantities in everyday life, specifically in regards to gasoline use for a car. We start with an initial total fuel capacity of 14.5 gallons. We then subtract the amount of fuel used for a trip to the grocery store, which is 1.5 gallons. This subtraction operation shows how much gasoline remains in the tank.
Step-by-step, the solution could be described like this:
Therefore the inequality representing the amount of gasoline left in the gas tank is 0 ≤ G ≤ 13, where G is the amount of gasoline left in the tank.
#SPJ12
Answer:
A midpoint is a point on a line segment that divide the segment into two equal segments.
Formula for finding midpoint with any two endpoints is;
Given two end points:
(3.5 , 2.2) and (1.5 , -4.8).
Let P(x, y) be the midpoint of (3.5 , 2.2) and (1.5 , -4.8).
By midpoint formula we have;
Simplify:
Therefore, the midpoint of the line segment with given endpoints is, (2.5, -1.3)
Answer: r = 22
Step-by-step explanation:
To answer this question, we can create a point-slope form equation.
y - y1 = m(x - x1)
y - r = 4(x - 4)
y - r = 4x - 16
y = 4x - 16 + r
Then, we will substitute the given point to solve for r.
y = 4x - 16 + r
(-14) = 4(-5) - 16 + r
(-14) = -20 - 16 + r
-14 = -36 + r
22 = r
Answer:
V=\frac{s}{t},where\ V-speed,\ s-distance\ ,t-time\\\\ v=\frac{\frac{3}{8}}{\frac{3}{4}}=\frac{3}{8}*\frac{4}{3}=\frac{4}{8}=\\\\0,5\frac{feet}{minute}\\\\ Speed\ is\ equal\ to\ 0,5\frac{feet}{minute}.
Step-by-step explanation:
1) 0,4x (5x – 6) + 7,2 = 2x (x + 0,6);
2) x (3x+2)-9 (x²-7x)=6x (10-x);
3) 12 (x³ - 2) -7x (x² − 1) = 5x³ +2x+6.
Answer:
Давайте рассмотрим каждое уравнение по очереди:
Уравнение: 0.4x(5x - 6) + 7.2 = 2x(x + 0.6)0.4x(5x−6)+7.2=2x(x+0.6)
Раскроем скобки:
2x^2 - 2.4x + 7.2 = 2x^2 + 1.2x2x
2
−2.4x+7.2=2x
2
+1.2x
Теперь выразим все в одну часть уравнения:
-2.4x + 7.2 = 1.2x−2.4x+7.2=1.2x
3.6x = 7.23.6x=7.2
x = 2x=2
Уравнение: x(3x+2) - 9(x^2 - 7x) = 6x(10 - x)x(3x+2)−9(x
2
−7x)=6x(10−x)
Раскроем скобки:
3x^2 + 2x - 9x^2 + 63x = 60x - 6x^23x
2
+2x−9x
2
+63x=60x−6x
2
Теперь выразим все в одну часть уравнения:
3x^2 - 9x^2 + 2x - 63x - 60x + 6x^2 = 03x
2
−9x
2
+2x−63x−60x+6x
2
=0
-3x^2 - 59x = 0−3x
2
−59x=0
x(-3x - 59) = 0x(−3x−59)=0
Отсюда получаем два возможных значения xx: x = 0x=0 или x = -\frac{59}{3}x=−
3
59
.
Уравнение: 12(x^3 - 2) - 7x(x^2 - 1) = 5x^3 + 2x + 612(x
3
−2)−7x(x
2
−1)=5x
3
+2x+6
Раскроем скобки:
12x^3 - 24 - 7x^3 + 7x = 5x^3 + 2x + 612x
3
−24−7x
3
+7x=5x
3
+2x+6
Теперь выразим все в одну часть уравнения:
5x^3 - 2x^3 + 7x - 2x - 24 - 6 = 05x
3
−2x
3
+7x−2x−24−6=0
3x^3 + 5x - 30 = 03x
3
+5x−30=0
Это уравнение не имеет очевидного решения, поэтому придется использовать численные методы для его решения.